Heterostructures through Divergent Edge Reconstruction in Nitrogen‐Doped Segmented Graphene Nanoribbons. Issue 37 (9th August 2016) - Marangoni, Tomas; Haberer, Danny; Rizzo, Daniel J.; Cloke, Ryan R.; Fischer, Felix R.
Abstract: Atomically precise engineering of defined segments within individual graphene nanoribbons (GNRs) represents a key enabling technology for the development of advanced functional device architectures. Here, the bottom‐up synthesis of chevron GNRs decorated with reactive functional groups derived from 9‐methyl‐9H‐carbazole is reported. Scanning tunneling and non‐contact atomic force microscopy reveal that a thermal activation of GNRs induces the rearrangement of the electron‐rich carbazole into an electron‐deficient phenanthridine. The selective chemical edge‐reconstruction of carbazole‐substituted chevron GNRs represents a practical strategy for the controlled fabrication of spatially defined GNR heterostructures from a single molecular precursor. Abstract : GNR, appetite for reconstruction : A new type of surface‐mediated ring‐expansion reaction has been used to create graphene nanoribbon (GNR) heterostructures, starting from a single molecular precursor. The newly developed GNR heterostructure is decorated with electron‐rich carbazole and electron‐deficient phenanthridine substituents along its edges. This new method paves the way toward the rational bottom‐up fabrication of GNR heterojunctions for functional device architectures (see figure).